(untitled) - EKONG, EKONG E. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
Conceptualizing change as a generally de-stablizing process, this study set out to investigate (a) the level of rural popular awareness of changes in the larger Nigerian society during the Military era, and (b) their patterns of adjustment to those changes. A total of 400 rural based respondents from the three states of the former Western State of Nigeria were involved in the study conducted in 1976/77. It was found that a large proportion of ruralites in Western Nigeria were aware of most of the changes which took place in the country during the military era but the extent to which they felt directly affected by the changes varied with the nature of the changes themselves. Similarly, their patterns of adjustment varied with the nature of the change and did not depend very much on personal characteristics. Instead the range of alternative behaviours available, the speed with which a change was expected to be effected, and the adaptability of such change to pre-existing behavioural patterns or culture, were very crucial in determining the mode of adjustment.